KONSEP MANUSIA MENURUT ISLAM - Sitti Rahmatiah (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam)
Regarding the process of the creation of man many theories appear before the revelation of the Koran. From the start the theory of Aristotle, Louis Pasteur, to Charles Darwin. They are trying to uncover about where the origin of life and living. Since then (exactly 1860) emerged a new theory which states that all life comes from previous life. Although the new theory seems to be more intense and irrational, but it is still not able to describe the